Biological control of Dactylopius opuntiae (Cockerell) using entomopathogenic fungi in Morocco - El Aalaoui, Mohamed; Rammali, Said; Sbaghi, Mohamed (Biocontrol science and technology, 2024)
In Morocco and many other Mediterranean countries, cultivation of Opuntia spp. has been severely impacted by infestations of Dactylopius opuntiae (Cockerell) (Hemiptera: Dactylopiidae). Several control approaches have been adopted worldwide to address the spread of this pest, including biological control. Many entomopathogenic fungal isolates (EPFs) have been described as promising agents for this purpose worldwide. The efficacy of three EPFs: Alternaria murispora (PP264308), Alternaria destruens (PP264311), and Macrophomina tecta (PP264310) against D. opuntiae young females and nymphs was assessed in laboratory and field settings. Under laboratory conditions, A. murispora and A. destruens at 10 8 conidia mL −1 , and D-limonene (the positive control) applied at 2.5 cc. L −1 , were the most effective, which resulted in significant mortality rates in adult females and nymphs (97%, 86%, and 93% respectively (adult females) and 100%, 98%, and 99% respectively (nymphs)) after 6 days of exposure, leading to LT 50 values of 3.0, 6.0 and 3.0 days, respectively (young female) and 3.0 (nymph). Under field conditions, A. murispora at 10 8 (88.9% mortality (nymphs) and 71.6% mortality (females)) and 10 7 conidia mL −1 (84.2% mortality (nymphs) and 64.2% mortality (females)), and D-limonene at 2.5 cc/L (88.8% mortality (nymphs) and 65.9% mortality (females)) showed the highest effectiveness in controlling D. opuntiae. We also observed that infected scale pests showed signs of mycosis, spore formation and discharge, which will contribute to the spread of the EPFs tested as biological control agents. Hence, alongside D-limonene, A. murispora, and A. destruens could be incorporated into an IPM strategy to control D. opuntiae.